Galactose:PEGamine coated gold nanoparticles adhere to filopodia and cause extrinsic apoptosis. Issue 2 (22nd November 2018) - Tzelepi, Konstantina; Espinosa Garcia, Cristina; Williams, Phil; Golding, Jon
Abstract : With increasing synthesis time, gold nanoparticles made with 50 : 50 α-galactose : PEGamine gradually lose ligands, show increased binding to filopodia, and become more toxic. Abstract : Ultra-small gold nanoparticles, surface functionalised with a 50 : 50 ratio of a thiolated α-galactose derivative and a thiolated hexaethylene glycol amine, are toxic to HSC-3 oral squamous carcinoma cells. Differences in nanoparticle toxicity were found to be related to the synthesis duration, with 1 h reaction nanoparticles being less toxic than 5 h reaction nanoparticles. The ligand density decreased with longer reaction time, although the size, charge and ligand ratio remained similar. The concentration of sodium borohydride in the reaction decreased logarithmically over 5 h but remained within a concentration range sufficient to desorb weakly bound ligands, possibly explaining the observed gradual decrease in ligand density. Nanoparticle toxicity was abrogated by inhibition of either caspase 3/7 or caspase 8, but not by inhibition of caspase 9, consistent with extrinsic apoptosis. Electron microscopic analysis of cellular uptake demonstrated predominantly cytoplasmic localization. However, when energy-dependent transport was inhibited, by lowering the temperature to 4 °C, a remarkable adhesion of nanoparticles to filopodia was observed. Inhibition of filopodial assembly with a fascin inhibitor prevented nanoparticle adhesion to HSC-3 cells at 4 °C, while fascin inhibition at 37 °C resulted in less cytoplasmic uptake. More adhesion to HSC-3 filopodia was seen with the higher toxicity 5 h reaction time nanoparticles than with the 1 h nanoparticles. By including two further cell types (HaCaT keratinocytes and hCMEC/D3 endothelial cells), a pattern of increasing toxicity with filopodial binding of 5 h reaction nanoparticles became apparent.